2012
DOI: 10.1016/j.mod.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Xmab21l3 mediates dorsoventral patterning in Xenopus laevis

Abstract: Specification of the dorsoventral (DV) axis is critical for the subsequent differentiation of regional fate in the primary germ layers of the vertebrate embryo. We have identified a novel factor that is essential for dorsal development in embryos of the frog Xenopus laevis. Misexpression of Xenopus mab21-like 3 (Xmab21l3) dorsalizes gastrula-stage mesoderm and neurula-stage ectoderm, while morpholino-mediated knockdown of Xmab21l3 inhibits dorsal differentiation of these embryonic germ layers. Xmab21l3 is a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…As mab21-l3 expression is positively regulated by foxi1 (ref. 24), there is a feedback relationship between foxi1 and mab21-l3 (see Fig. 9d).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As mab21-l3 expression is positively regulated by foxi1 (ref. 24), there is a feedback relationship between foxi1 and mab21-l3 (see Fig. 9d).…”
Section: Discussionmentioning
confidence: 97%
“…During our screen identifying genes that show a characteristic expression pattern in the embryonic epithelium, we found that an evolutionarily conserved gene, mab21-l3, showed a salt-andpepper pattern of expression (see below). Mab21 was first identified in Caenorhabditis elegans, and three orthologous genes, mab21-like 1 (mab21-l1), mab21-like 2 (mab21-l2) and mab21-l3, have been identified in vertebrates 23,24 . Among these three genes, mab21-l3 has been poorly studied.…”
Section: Xenopus Mab21-l3 Is Expressed In Both Mccs and A-ionocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas MAB21 is required for pattern formation of the male tail in nematodes, MAB21 is sufficient and required for development of the dorso-ventral axis in vertebrates103334. MAB21 proteins act downstream of the TGF-β signaling pathway by antagonizing the effect of BMP4 in Xenopus embryo ventralization and in C. elegans MAB21 is negatively regulated by cet-1 (vertebrate BMP4)22.…”
Section: Discussionmentioning
confidence: 99%